2022
DOI: 10.21203/rs.3.rs-1943634/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self /other recognition and distinction in adolescents’ with Anorexia Nervosa: a double mirror paradigm

Abstract: Background The body plays a major role in defining, understanding and treating anorexia nervosa. Much research has focused on patients' physical body representation or their own perceived body, but without explicit reference to their relationship to others and the social processes involved. Yet, there are a several arguments supporting impairments in interpersonal relationships in these patients. Notably, some evidence suggests that self/other distinction (SOD), the ability to distinguish one's own body, acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 92 publications
0
8
0
Order By: Relevance
“…The main characteristics and results of the 32 included studies are summarised in Appendix C. Studies were published between the years 2006 and 2022 in the English language. Thirty studies were published in peer-reviewed journals and two were from the grey literature (Lavenne-Collot et al, 2022; Wolf et al, 2021). Sample sizes ranged from six to 167, with a median of 36.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The main characteristics and results of the 32 included studies are summarised in Appendix C. Studies were published between the years 2006 and 2022 in the English language. Thirty studies were published in peer-reviewed journals and two were from the grey literature (Lavenne-Collot et al, 2022; Wolf et al, 2021). Sample sizes ranged from six to 167, with a median of 36.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies examined differences in susceptibility to embodiment illusions as a function of BID. Nine (64.29%) reported significantly greater susceptibility amongst those with high (relative to low/no) BID on at least one outcome measure (generally involving medium or large-sized effects; Eshkevari et al, 2012; 2014; Kaplan et al, 2014; Keizer et al, 2014; 2016; Lavenne-Collot et al, 2022; Metral et al, 2017; Mussap & Salton, 2006; Zopf et al, 2016). Three (21.43%) studies reported reduced susceptibility among those with high (relative to low/no) BID on at least one measure, involving medium and large effects (Carey & Preston, 2019; Porras-Garcia et al, 2020; Tagini et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations